Differentiation of lard from other fat in pastry products using fourier transform infrared spectroscopy combined multivariate analysis - Mohamed Rani, Wan Siti Farizan (2014)
The determination of lard in pastry products is increasing important in the food industry. Hence, this study was used Fourier transform infrared (FTIR) spectroscopy combined with chemometric analysis for investigating the lard adulteration in the pastry products. The objectives of the study were to apply FTIR spectroscopy for detection and quantification of lard in locally manufactured pastry products and to use the combination of FTIR spectroscopy and chemometric in qualitative and quantitative analysis of lard in pastry. The first objective employed 45 samples of extracted oil from pastries prepared in laboratory (SP samples). These SP samples (with known amount of adulterants) served as training set prior to classify the unknown edible oils extracted from 50 commercial pastries available in the market (CP samples). Since edible oils spectra seems similar through visual inspection,chemometrics analysis of partial least square (PLS)-second derivate and discriminant (DA) analysis have been proposed to quantify and classify the presence of lard. Subsequently, FTIR spectra were calculated at selected region of 1200-900cm-1 and also have treated with their normal, first and second derivatives. From the analysis, PLS-second derivative offers excellent relationship between FTIR-actual and predicted values with R2 and RMSEC of 0.994 and 2.38, respectively. The highest R2 and lowest values of RMSEC computed indicated minimum average error and goodness of the developed calibration set. The classification results showed DA and Coomans plot models were precisely grouped CP samples according to intensity of adulteration with 6 principal components (PCs) and 100% of variability described. In the second objective, qualitative and quantitative analysis of lard were performed by discriminant analysis (DA) and visualized as Coomans plot. DA and Coomans plot were successfully classified commercial baking fats and shortening to their respective axis of lard adulteration as lowest as 0.25ml (v/v) with high R2 and low RMSECV in normal data pretreatment of 4.36 and 0.97, respectively. The data sets were validated by normal, first and second data pre-treatment,baseline variation, calibration design and constrained mixtures of PLS. The data sets were split randomly into calibration (n = 141) and validation (n = 141) samples. Coefficient of determination (R2) and standard error in cross validation (SECV) also were calculated. Prediction accuracy of FTIR calibration models were tested using validation set and evaluated by standard error of prediction (SEP), slope and bias. The study indicated that, FTIR spectroscopy combined with chemometric multivariate analysis provided as a rapid technique in determining lard adulteration in pastry products at regions of interest.